2023
DOI: 10.18632/aging.204455
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bioinformatics analysis reveals the significance of forkhead box family members in pancreatic adenocarcinoma

Abstract: Background: Forkhead box proteins (FOXs) play important roles in multiple biological processes; while little is known regarding the role of FOX members in pancreatic adenocarcinoma (PAAD). This study aimed to comprehensively investigate the function of FOX family members in PAAD. Methods: Expression and prognostic value of FOXs were analyzed by R language and GEPIA. Genetic alteration and promoter methylation level were analyzed using CBioPortal and UALCAN. Protein-protein interactions and gene functions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have proved that FOXA1 is a vital transcription factor in the occurrence and development of LC, and its overexpression can enhance cell metastasis and proliferation [27,28]. However, the effect of FOXA1 on LC cell aging has not been reported, but previous study showed that the expression of FOXA1 was negatively correlated with the aging marker IL-6 level [29]. Further, Yusuke Imamura et al [30] reported that the depletion of FOXA1 can increase P21 expression in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that FOXA1 is a vital transcription factor in the occurrence and development of LC, and its overexpression can enhance cell metastasis and proliferation [27,28]. However, the effect of FOXA1 on LC cell aging has not been reported, but previous study showed that the expression of FOXA1 was negatively correlated with the aging marker IL-6 level [29]. Further, Yusuke Imamura et al [30] reported that the depletion of FOXA1 can increase P21 expression in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The forkhead box (FOX) proteins constitute a family of transcription factors characterized by their well-preserved fork-head and winged-helix DNA binding domains, which display a specific affinity for the universally conserved DNA sequence 5ʹ-TTGTTTAC-3ʹ ( 20 , 21 , 22 ). FOXK, comprising FOXK1 and FOXK2, harbor a forkhead-associated (FHA) domain rich in phospho-threonine-residues that distinguishes it from other FOX transcription factors ( 23 ).…”
mentioning
confidence: 99%